2021
DOI: 10.1017/dem.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Economic returns of family planning and fertility decline in India, 1991–2061

Abstract: Investment in family planning (FP) provides returns through a lifetime. Global evidence shows that FP is the second-best buy in terms of return on investment after liberalizing trade. In this study, we estimate the cumulative benefits of FP investments for India from 1991 to 2016 and project them up to 2061 with four scenarios of fertility levels. The findings suggest that India will have greater elasticity of FP investments to lifetime economic returns compared to the world average (cost–revenue ratio of 1:12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
3
7
0
1
Order By: Relevance
“…We choose UN South Asia as a regional model life table for population projection. Our assumption is in line with Stover, Heaton, and Ross (2006) and Goli et al (2021) which found the South Asian model to be more consistent for mortality estimates for India.…”
Section: Model Life Tablessupporting
confidence: 90%
See 4 more Smart Citations
“…We choose UN South Asia as a regional model life table for population projection. Our assumption is in line with Stover, Heaton, and Ross (2006) and Goli et al (2021) which found the South Asian model to be more consistent for mortality estimates for India.…”
Section: Model Life Tablessupporting
confidence: 90%
“…Despite this, it is believed that rising urbanisation and improved status of women with rising literacy rate can improve SRB in future (Goli et al 2021). We assume in the Demographic-Emphasis Scenario that SRB will improve and stabilize at 108 boys per hundred girls at birth by 2061, which is in line with the projections made by United Nations (2019).…”
Section: Sex Ratio At Birth (Srb)supporting
confidence: 60%
See 3 more Smart Citations